Association of working hours and cumulative fatigue among Chinese primary health care professionals - Lu, Yushi; Li, Zhi; Chen, Qingsong; Fan, Yuting; Wang, Jin; Ye, Yonghao; Chen, Yongqi; Zhong, Tian; Wang, Ling; Xiao, Ying; Zhang, Dongmei; Yu, Xi (Frontiers in Public Health, 2023)
Introduction: The association between long working hours and cumulative fatigue is widely acknowledged in the literature. However, there are few studies on the mediating effect of working hours on cumulative fatigue using occupational stress as a mediating variable. The present study aimed at investigating the mediating role of occupational stress in the relationship between working hours and cumulative fatigue in a sample of 1327 primary health care professionals. Methods: The Core Occupational Stress Scale and the Workers' Fatigue Accumulation Self-Diagnosis Scale were utilized in this study. The mediating effect of occupational stress was examined using hierarchical regression analysis and the Bootstrap test. Results: Working hours were positively associated with cumulative fatigue via occupational stress (p < 0.01). Occupational stress was found to partially mediate the relationship between working hours and cumulative fatigue, with a mediating effect of 0.078 (95% CI: 0.043–0.115, p < 0.01), and the percentage of occupational stress mediating effect was 28.3%. Discussion: Working hours can be associated with cumulative fatigue either directly or indirectly via occupational stress. As a result, by reducing occupational stress, primary health care professionals may reduce the cumulative fatigue symptoms caused by long hours of work.